The Analysis of Language Style of Gurindam Dua Belas Written by Raja Ali Haji - Muhammad Zulfadhli; Agustin Lakawa Rebecca Lakawa (Universitas Pendidikan Indonesia, 2022)
This research emphasizes on the importance of exploring the language style of Raja Ali Haji’s Gurindam Dua Belas which is implicitly conveyed through diction, parallelism, and figure of speech. This study conducted qualitatively focusing on descriptive analysis in which data was taken from the book of Raja Ali Haji’s Gurindam Dua Belas. The book consists of 12-Articles published in collaboration between the City Government of Tanjungpinang and The Foundation of Panggung Melayu. This is a documentation study by using triangulation technique of analysis covering data reduction, data presentation, and data conclusion. The results show that there are 66 specific dictions and 17 general dictions found in the book. In addition, the analysis of language style is also related to parallelism in which intermittent parallelism has differences in its location which can be found in 11 out of 12 Articles of Raja Ali Haji’s Gurindam Dua Belas. Whereas, rarely used parallelism, the repetition of syllables or phrases at the same positions is only found in 1 out of 12 Articles. Finally, the analysis of language style is correlated to the largest figures of speech which is 44 metaphorical figures, while the smallest is 5 sinekdoke figures. In conclusion, language style is an effective means of providing teaching guidance by showing the beauty of literary works. This signifies the importance of language styles as a means of expressing messages depicted from Raja Ali Haji’s Gurindam Dua Belas.